Influences of distributed propulsion system parameters on aerodynamic characteristics of a BLI-BWB UAV (Xibei Gongye Daxue Xuebao, 2021)
Focusing on the aerodynamic characteristics of the blended wing body (BWB) aircraft with boundary layer ingestion(BLI) distributed propulsion system; the influences of propulsion system parameters under the condition of cruise and takeoff are studied. Firstly, based on the momentum source method (MSM), the NASA ducted propeller model is simulated, which verifies the reliability of the numerical method in this paper. Then, by using the method of structural grid and S-A turbulence model to solve the Reynolds averaged Navier-Stokes (RANS) equation, the aerodynamic characteristics of the BLI UAV model with D80 ducted fan in cruise state are numerically calculated. It is proved that the advantage of the BLI distributed propulsion system is superior in increasing lift. And the aerodynamic characteristics of the BLI UAV with different propulsion system parameters are compared. At last, the aerodynamic effect of ducted fan thrust on the BLI UAV is carried out. The results show that, due to the suction function of the BLI distributed propulsion system, the air flow velocity near the BWB fuselage is effectively accelerated, and the flow along the spanwise is restrained, which improves the lift coefficient about 16% and lift-to-drag ratio about 10%. Under the condition of equal thrust, the D80 ducted fan brings larger load of the propeller, which makes the static pressure at the inlet and outlet smaller. Compared with D150 ducted fan, the lift-to-drag ratio is increased by 15%. When aircraft takes off, increasing the thrust of the ducted fan can reduce the possibility of flow separation on the upper surface of the fuselage, which is conducive to the safety.